Immediate Effects of Dynamic Cupping on Shoulder Active Range of Motion of Senior Male Handball Players: A Randomized Controlled Trial - Ricardo Cardoso; Adérito Seixas; Isabel Moreira-Silva; Joana Azevedo; Diogo Duarte (Applied Sciences)
Background: Shoulder injuries are common among handball players and have been associated with adjustments in shoulder mobility with decreased flexibility. The aim of the study is to analyze the immediate effects of dynamic cupping on shoulder active range of motion (AROM) of senior male handball players. Materials and Methods: A total of 80 senior male handball players completed a socio-demographic and clinical questionnaire. They were then randomly divided into two groups: the Intervention Group (IG; n = 40), which received dynamic cupping therapy, and the Control Group (CG; n = 40), which did not receive any intervention. Shoulder AROM, including flexion, extension, abduction, adduction, horizontal adduction, horizontal abduction, internal rotation, and external rotation, was assessed in both groups before the intervention (M0) and after the intervention (M1). Results: After the intervention, the IG showed a statistically significant increase in AROM for all shoulder movements. In contrast, the CG only demonstrated significant improvements in internal rotation (p = 0.042), adduction (p = 0.011), horizontal abduction (p = 0.004), and horizontal adduction (p = 0.005). Additionally, the IG exhibited a statistically significant increase in shoulder AROM across all movements compared to the CG at M1. Conclusions: The findings of this study support that dynamic cupping enhances shoulder AROM in senior male handball players.